Discourse Analysis on International Online News Reports of Manchester Bombing - Nazmi, Nurul Fatihah Muhamad; Ab Rashid, Radzuwan; Zani, Nurul Afiqah Muhammad; Jabar, Nor Fatin Abdul; Aziz, Muhammad Farriz (International Journal of Asian Social Science, 2018)
Since September 11 attack, Islam has always been getting the spotlight whenever news of terrorisms are reported in the media. The issue of terrorism is further heated when it was held responsible by Muslims. Media has a major influence in framing the issues while reporting the news. This paper aims to provide insights into two different international online news reports on Manchester Bombing in United Kingdom on 22 May 2017. The reports were examined using a discourse analysis approach centring on Rhetorical Structures, and Grammatical Analysis. While both articles seem not taking side and being bias towards each group of interest, The Washington Post appears to be more inclined towards dragging the trivial info regarding the perpetrator (i.e family and faith) and what is called as supposition of the ongoing investigation into the news report. Meanwhile Aljazeera is seen to be stressing more on the outlook of Muslims concerning the act of terror by pointing out multiple voices from Muslim community to make sure the audience knows where Muslims stand on this matter. The analysis shows that the online news reports in Washington Posts has the propensity to report the news in singular perspective in which the focus is merely on the suspect and anything that come with him so, it opens the path for readers to construct their own interpretation of the whole situation. Meanwhile, Aljazeera leans on illuminating the issue in broader perspectives by providing multiple insights into the issue be it from the Muslim and the heterogeneous community in Britain to come together in the wake of the horrific incident.